Lignocellulosic waste pretreatment solely via biocatalysis as a partial simultaneous lignino-holocellulolysis process - Angadam, J.O. (MDPI, 2021)
Human endeavors generate a significant quantity of bio-waste, even lignocellulosic waste, due to rapid industrialization and urbanization, and can cause pollution to aquatic ecosystems, and contribute to detrimental animal and human health because of the toxicity of consequent hydrolysis products. This paper contributes to a new understanding of the lignocellulosic waste bio-pretreatment process from a literature review, which can provide better biorefinery operational outcomes. The simultaneous partial biological lignin, cellulose and hemicellulose lysis, i.e., simultaneous semi-lignino-holocellulolysis, is aimed at suggesting that when ligninolysis ensues, holocellulolysis is simultaneously performed for milled lignocellulosic waste instead of having a sequential process of initial ligninolysis and subsequent holocellulolysis as is currently the norm. It is presumed that such a process can be solely performed by digestive enzyme cocktails from the monkey cups of species such as Nepenthes, white and brown rot fungi, and some plant exudates. From the literature review, it was evident that the pretreatment of milled lignocellulosic waste is largely incomplete, and ligninolysis including holocellulolysis ensues simultaneously when the waste is milled. It is further proposed that lignocellulosic waste pretreatment can be facilitated using an environmentally friendly approach solely using biological means. For such a process to be understood and applied on an industrial scale, an interdisciplinary approach using process engineering and microbiology techniques is required. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.